Social Sustainability in Late Adolescence: Trait Emotional Intelligence Mediates the Impact of the Dark Triad on Altruism and Equity - Giancola, Marco; Palmiero, Massimiliano; D’Amico, Simonetta (Frontiers in Psychology, 2022)
Adolescence involves profound changes that affect individuals’ lives in different ways. Amongst others, adolescence also yields an enhanced awareness and responsibility toward the community, representing a critical age to develop pro-social behaviours. In the present study, the mediation role of Trait Emotional Intelligence (TEI) was detected for the relationship between the Dark Triad and pro-social behaviour based on altruism and equity. One-hundred and twenty-nine healthy late adolescents filled in the Dark Triad Dirty Dozen, measuring Machiavellianism, psychopathy, and narcissism, the Altruistic Action Scale, evaluating behaviours directed at helping others, the Equity Scale, assessing behaviours directed at equity in different forms, and the Trait Emotional Intelligence Questionnaire-Short Form. Results showed that TEI mediated the negative effect of the three Dark Triad traits on both altruism and equity. This finding confirms that TEI relies on a set of dispositions (e.g., emotional management of others, social competence and empathy), which reduce the malevolent effects of the Dark Triad on altruism and equitable behaviour in late adolescence. This led to assume that intervention programs focused on improving emotional skills, also in late adolescence, can promote pro-sociality.